Martial, Book IV : a commentary - Moreno Soldevila, Rosario. (Mnemosyne, Supplements, 2006)
This volume is the first comprehensive commentary on the fourth book of Martial's epigrams. The introduction discusses its date of publication, major themes (Domitian, literature, death), the arrangement and form of the epigrams, and some issues concerning the transmission of the text. Of special note is the author's study of the structure of the book. The commentary, preceded by the Latin critical text and an English translation, aims to provide readers with as much pertinent information as possible to enable them to fully comprehend the epigrams. Attention is paid to style and literary tradition, as well as to realia. Both each individual epigram and the book as a whole are studied as finely accomplished works of art.